2010
DOI: 10.1007/s10705-010-9390-4
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and environmental aspects of phosphate fertilizers varying in source and solubility: an update review

Abstract: This review discusses and summarizes the latest reports regarding the agronomic utilization and potential environmental effects of different types of phosphate (P) fertilizers that vary in solubility. The agronomic effectiveness of P fertilizer can be influenced by the following factors: (1) water and citrate solubility; (2) chemical composition of solid watersoluble P (WSP) fertilizers; (3) fluid and solid forms of WSP fertilizers; and (4) chemical reactions of P fertilizers in soils. Non-conventional P ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
163
0
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(186 citation statements)
references
References 116 publications
(103 reference statements)
6
163
0
17
Order By: Relevance
“…This shows that the application of litter to the soil surface without tillage increased the P content in the surface layer over the years, in agreement with the data obtained by Gatiboni et al (2007Gatiboni et al ( , 2008 and Ceretta et al (2010a). These authors also reported that part of the P applied, regardless of its origin, accumulates preferentially in organic forms in the soil, and can be bioavailable to crops (Santos et al, 2008;Pavinato et al, 2009), but increases potential losses through surface runoff (Ajmone-Marsan et al, 2006;Gatiboni et al, 2007;Hao et al, 2008;Ceretta et al, 2010b;Chien et al, 2011). The low P export in maize grain, harvested only once a year, together with low rates of soil loss because of adoption of the no-till system may also have contributed to P accumulation, detected by different extractants (Figures 1a, b, c, d), in the soil surface layer, which agrees with the data obtained by Durigon et al (2002) and Ceretta et al (2003) in natural pastures with a history of application of pig litter and low P export.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This shows that the application of litter to the soil surface without tillage increased the P content in the surface layer over the years, in agreement with the data obtained by Gatiboni et al (2007Gatiboni et al ( , 2008 and Ceretta et al (2010a). These authors also reported that part of the P applied, regardless of its origin, accumulates preferentially in organic forms in the soil, and can be bioavailable to crops (Santos et al, 2008;Pavinato et al, 2009), but increases potential losses through surface runoff (Ajmone-Marsan et al, 2006;Gatiboni et al, 2007;Hao et al, 2008;Ceretta et al, 2010b;Chien et al, 2011). The low P export in maize grain, harvested only once a year, together with low rates of soil loss because of adoption of the no-till system may also have contributed to P accumulation, detected by different extractants (Figures 1a, b, c, d), in the soil surface layer, which agrees with the data obtained by Durigon et al (2002) and Ceretta et al (2003) in natural pastures with a history of application of pig litter and low P export.…”
Section: Resultssupporting
confidence: 80%
“…In addition, adjustments of the adsorption isotherm by other models, as that proposed by Koski-Vähälä & Hartikainem (2001), aggregate the quantity of water-desorbed P (Q o ), allowing a calculation of the P concentration required in the solution for half of maximum adsorption (km) and the equilibrium P concentration (ECP) (Koski-Vähälä & Hartikainem, 2001;Sinaj et al, 2002). This last parameter may be used as an environmental indicator to foresee the possibilities of leaching to subsurface waters and of runoff to surface water bodies (AjmoneMarsan et al, 2006;Gatiboni et al, 2007Gatiboni et al, , 2008Hao et al, 2008;Chien et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The high solubility of MAP, associated with the lower adsorption potential of the soil, resulted in a higher availability of P already in the first cultivation. This difference was not observed in the clay loam soil due to the higher clay content and higher adsorption potential (Chien et al, 2011). Ferreira (2014 found higher available P contents in a Latossolo Vermelho distroférrico (clay loam dystrophic Oxisol) and in a Neossolo Quartzarênico distrófico (sandy loam Psament) when corn plants were fertilized with soluble phosphates (granulated MAP and triple superphosphate, as well as MAP diluted in water), instead of OMF (poultry litter plus granular Table 1.…”
Section: Resultsmentioning
confidence: 92%
“…No entanto, a disponibilização de P pela aplicação de FN é sensível às elevações nos teores de Ca, aos aumentos no pH e à queda do teor de umidade do solo, além da pequena área de contato solo/fertilizante quando é aplicado sobre as pastagens, desfavorecendo-o na comparação aos fosfatos solúveis. Entretanto, em solos ácidos (pH < 5,2) e com baixos teores de Ca, a eficiência agronômica dos FN em longo prazo pode ser suficientemente elevada para obterem-se rendimentos compatíveis à aplicação dos fosfatos solúveis (Gatiboni et al, 2003;Chien et al, 2011), apresentando-se adequados para o uso em culturas perenes (Szilas et al, 2007). Nesse sentido, Tiecher et al (2013) demonstraram que após 154 meses o teor de P disponível no solo e a produção anual de forragem foram equivalentes com a aplicação de hiperfosfato de Gafsa e fosfatos solúveis.…”
Section: Introductionunclassified